Extensive anogenital lichen sclerosus with vaginal stenosis: A case report - Ahmed Samy El-agwany (Wolters Kluwer Medknow Publications, 2015)
Lichen sclerosus (LS) is an acquired, chronic, inflammatory, fibrotic and atrophic disease, usually affecting skin, particularly genital region. It affects women, with a median age of 50 years. No etiological factor is actually known. Here we have described a case of a woman affected by extensive anogenital lichen sclerosus complicated with vaginal stenosis.